2021
DOI: 10.3233/ch-200978
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fibrinogen and fibrin degradation product are associated with poor outcome in COVID-19 patients: A meta-analysis

Abstract: INTRODUCTION: COVID-19 is a systemic infection with a significant impact on coagulation which manifests in thromboembolism. There is an unknown relationship of which coagulation profile parameter at presentation has an association with poor outcome in COVID-19. OBJECTIVE: This meta-analysis aimed to determine the relationship between fibrinogen and FDP with poor outcome in COVID-19 patients. METHODS: A systematic search of all observational studies or trials involving adult patients with COVID-19 that had any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
(34 reference statements)
0
19
0
4
Order By: Relevance
“…Specifically, elevations in fibrinogen, fibrinogen degradation product, C-reactive protein (CRP), interleukin-6 (IL-6), erythrocyte sedimentation rate (ESR), and D-dimer have been found to be associated with increased severity of disease. [16][17][18] Severe thrombocytopenia and lymphopenia have also been associated with poorer outcomes, both independently and in the setting of disseminated intravascular coagulation (DIC). 19,20 Obtaining these clinical parameters may provide further information for the prediction of VTE (as discussed below) as well as overall prognosis.…”
Section: Clinic Al Char Ac Teris Tic Smentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, elevations in fibrinogen, fibrinogen degradation product, C-reactive protein (CRP), interleukin-6 (IL-6), erythrocyte sedimentation rate (ESR), and D-dimer have been found to be associated with increased severity of disease. [16][17][18] Severe thrombocytopenia and lymphopenia have also been associated with poorer outcomes, both independently and in the setting of disseminated intravascular coagulation (DIC). 19,20 Obtaining these clinical parameters may provide further information for the prediction of VTE (as discussed below) as well as overall prognosis.…”
Section: Clinic Al Char Ac Teris Tic Smentioning
confidence: 99%
“…Hematologic and inflammatory laboratory abnormalities have been found to correlate with disease severity in patients with COVID‐19. Specifically, elevations in fibrinogen, fibrinogen degradation product, C‐reactive protein (CRP), interleukin‐6 (IL‐6), erythrocyte sedimentation rate (ESR), and D‐dimer have been found to be associated with increased severity of disease 16‐18 . Severe thrombocytopenia and lymphopenia have also been associated with poorer outcomes, both independently and in the setting of disseminated intravascular coagulation (DIC) 19,20 .…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“… 56 In the current study, we found that high level of fibrinogen at admission significantly increased the risk of developing severe COVID-19. The results from a meta-analysis showed that the mean fibrinogen value at admission was significantly higher in patients with severe COVID-19 than in those with non-severe disease, 57 which suggests that high fibrinogen level can also serve as a marker of poor prognosis in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The Roles of Fibrinogen in Inflammation and Infection Appropriate levels of fibrinogen, a glycol protein secreted from the liver, are required for hemostasis and homeostasis 23 , and levels can reflect injury, inflammation and infection [24][25][26] . In pediatric sepsis, fibrinogen levels lower than 2 g/L are strongly associated with higher risk of death 27 , while in COVID-19 patients, elevated fibrinogen level is associated with higher risk of a poor outcome 28 . Previous studies have suggested that fibrinogen has potential for diagnosing PJI before revision hip and knee arthroplasty 17,29,30 .…”
Section: The Incidence Of Preexisting Fixation-related Infection (Fri)mentioning
confidence: 99%